2016
DOI: 10.1515/ijafr-2016-0007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a bacteriophage cocktail in combination with modified atmosphere packaging in controlling Listeria monocytogenes on fresh-cut spinach

Abstract: A Listeria monocytogenes-specific bacteriophage cocktail was evaluated for its activity against a nalidixic acid-resistant L. monocytogenes (Lm-NalR) isolate on fresh-cut spinach stored under modified atmosphere packaging at various temperatures. Pieces (~2 × 2 cm2) of fresh spinach inoculated with 4.5 log CFU/cm2 Lm-NalR were sprayed with the phage cocktail (6.5 log plaque-forming units [PFU]/cm2) or a control. The samples were stored at 4°C or 10°C for up to 14 d in sealed packages filled with either atmosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…There, results showed growth potentials on spinach, where initial concentrations 2.28 ± 0.47 log 10 cfu g −1 at 8 • C led to maximum population densities of 5.85 ± 0.67 log 10 cfu g −1 over 16 days. With high initial inoculum densities of around 10 5 cfu g −1 , growth of L. monocytogenes was identified on freshly cut spinach leaves in ambient and modified atmosphere (low O 2 , high CO 2 ) over 14 days at 10 • C storage [28]. Interestingly, under ambient atmosphere (filled with atmospheric air), cfu g −1 values dropped at day 7, but recovered subsequently to around 10 6 cfu g −1 by day 10.…”
Section: Discussionmentioning
confidence: 99%
“…There, results showed growth potentials on spinach, where initial concentrations 2.28 ± 0.47 log 10 cfu g −1 at 8 • C led to maximum population densities of 5.85 ± 0.67 log 10 cfu g −1 over 16 days. With high initial inoculum densities of around 10 5 cfu g −1 , growth of L. monocytogenes was identified on freshly cut spinach leaves in ambient and modified atmosphere (low O 2 , high CO 2 ) over 14 days at 10 • C storage [28]. Interestingly, under ambient atmosphere (filled with atmospheric air), cfu g −1 values dropped at day 7, but recovered subsequently to around 10 6 cfu g −1 by day 10.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of environmental conditions on L. monocytogenes on leafy vegetables has been well-established. The application of different atmosphere treatments has been indifferent to the limited impact of the growth of L. monocytogenes on leafy vegetable products [15][16][17]. Incubation over 6 days at 7 • C, combination of 7 • C and 15 • C, and solely 15 • C showed increasing growth potentials of L. monocytogenes on spinach and rocket with an increase in temperature [18].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study by Boyacioglu and colleagues showed that under different O 2 and CO 2 concentrations, the phage cocktail had no significant effect on the killing effect of Escherichia coli O157:H7 37 . They also found that there was no significant difference in the inhibitory effect of bacteriophages on Listeria monocytogenes under controlled atmosphere storage conditions and normal pressure storage conditions 38 . On the other hand, Tanji and colleagues reported that, under aerobic conditions, the optical density (OD) value of phage mixture (SP15‐21‐22) lysing E. coli O157:H7 decreased more than that under anaerobic conditions 39 .…”
Section: Efficacy Of Bacteriophage As An Antibacterial Agents Is Affe...mentioning
confidence: 99%
“…37 They also found that there was no significant difference in the inhibitory effect of bacteriophages on Listeria monocytogenes under controlled atmosphere storage conditions and normal pressure storage conditions. 38 On the other hand, Tanji and colleagues reported that, under aerobic conditions, the optical density (OD) value of phage mixture (SP15-21-22) lysing E. coli O157:H7 decreased more than that under anaerobic conditions. 39 Another study conducted by Mizuno et al showed that, under anaerobic conditions, the ability of bacteriophage CrRp3 to lyse enteropathogenic E. coli was significantly delayed.…”
Section: Initial Bacteriophage Titermentioning
confidence: 99%